Odpowiedzi

2009-11-21T17:14:18+01:00
A) 35ab do 2 + 7ab = 7ab(5ab+1)
b) 2ba do 2 b do 2 - 13a = a(2b²-13)
c) 1/2xy do 2 - 1/4 xy = 1/4xy(1/4xy-1)
d) 1/3 ab do 3 - 1/9 a do 2 b do 2= ab²(1/3ab-1/9)
2009-11-21T17:28:20+01:00
A) 35ab do 2 + 7ab = 7ab(5ab+1)
b) 2ba do 2 b do 2 - 13a = a(2b²-13)
c) 1/2xy do 2 - 1/4 xy = 1/4xy(1/4xy-1)
d) 1/3 ab do 3 - 1/9 a do 2 b do 2= ab²(1/3ab-1/9)
2009-11-21T17:31:14+01:00
A) 35ab do 2 + 7ab=7ab(5ab+1)
b) 2ba do 2 b do 2 - 13a=a(2b²-13)
c) 1/2xy do 2 - 1/4 xy=1/4xy(1/4xy-1)
d) 1/3 ab do 3 - 1/9 a do 2 b do 2=ab²(1/3ab-1/9)